An Innovation Center Model to Transform Health Systems to Improve Care of Older Adults. Issue 1 (13th November 2019) - Allen, Kyle; Hazelett, Susan; Martin, Michael; Jensen, Christine
Abstract : The US population is aging faster than at any other time in our history. This growth, coupled with a slow adaptive health policy framework, is creating an urgent need to reengineer and improve the quality, safety, and cost‐effectiveness of health systems to meet the needs of older adults and embrace the success we have achieved with longevity. Without rapid adoption of evidence‐based models that are known to improve safety and health outcomes, we significantly jeopardize the lives of thousands of older adults receiving care under our current health systems' processes and models. This article describes an innovation and operations infrastructure that was successfully tested in two independent and geographically distinct community health systems. This operations and implementation framework can be scaled and used to accelerate the changes needed to improve care for older adults in health systems throughout the United States. J Am Geriatr Soc 68:15–22, 2019